MORPHOTECTONIC STUDY OF JABIL MAKHUL AREA BY USING SATELLITE IMAGES - Hussain, Amera (Iraqi Journal of Science, 2024)
The research includes a morphotectonic study of Mukhul anticline which located to the north of Baiji in city of Tikrit which is north of Baghdad.The study is based on remote sensing data such as image taken by Digital Globe (2005)with three bands(1,2,3) and Terra Metric , Europe Technologies (2005) image and topographic map in addition to different geological maps from various sources as well as the field work.According to the previous data sources a geomorphologic classification carried out on the bases of genetic origin by using false colour images. The geomorphologic map has been prepared with location of different geomorphologic units as well as the morphotectonic map of the area.Various types of drainage patterns identified in the area also longitudinal section of three valleys were plotted and some anomalies in the upward concavity of the longitudinal section were analyzed.The index of sinuosity of the Tigris river calculated in (14) station on the river which interprets the tectonic of the studied area.